Monitoring System Building Plan For Risk Of Civil Office - Rahayu, Sri; Faris, Muhammad Rofi; Pane, Asni Ramadani (APTISI Transactions on Management (ATM), 2020)
The development of increasingly rapid information technology requires companies to have a system that is able to provide data and information quickly and accurately. Tangerang Regency Education Office is a government agency in charge of controlling the education sector. In its business process, the Education Office still faces difficulties in obtaining reports on employment in periodic salary increases, because the system used is still using the help of Microsoft excel application software that is semi computerized, so that every data reported often has errors in providing civil servant salaries. Based on these problems Tangerang District Education Office is in dire need of an automated computer system that can control the regular salary increases of civil servants effectively and efficiently. As a tool to help in object-oriented programming language, Unified Modeling Language (UML) is used to describe the system, while data collection techniques use observation, interview, and literature study methods, so that the system can be monitored properly, effectively and efficiently using MySql databases, and PHP.